The contractual landscape and the protection of consumers in online auction contracts - Khan, Haleema (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Resale price maintenance in consumer good markets: an economic justification for the prohibition of RPM - Schwaderer, Melanie Ariane (European University Institute, 2019)
The thesis contributes to the debate on the EU’s approach to the business practice of resale price maintenance (RPM), which is widely criticized as too strict and in conflict with what is considered to be the consensus in the economic literature. The thesis critically dissects the economic consensus, on which the critique against the EU’s approach is based, by analyzing the empirical evidence that is cited to support the claim that RPM can frequently be explained by the service-based RPM models and shows that there is no convincing evidence that would support the significance of these positive RPM models that predict positive effects on welfare. To support this finding the thesis collects new evidence by surveying the marketing literature and shows that not only is there no convincing evidence that the positive RPM models frequently apply, but to the contrary there is evidence that these models are inconsistent with the real world phenomenon of RPM. Having refuted the service-based models the thesis takes up the scientific challenge that “it takes a theory to beat a theory” and proposes to fill the gap with three price-based models. The thesis offers an analysis of the three price-based RPM models, first from the perspective of welfare effects and then from a broader economic perspective in an attempt to ultimately show that the EU approach to RPM can be justified based on these economic models. All three models explain the situation in which RPM is used by a branded good manufacturer to create the perception of high quality, which is used either as a credible quality signal, becomes a component of the product or is used to bias the consumer decision; they thus enter the difficult terrain of consumer preference formation and of markets for the intangible components of a product.
Keywords: Competencia; Competition law; European Union countries; Marketing; Price maintenance